2016
DOI: 10.1177/0961203316684212
|View full text |Cite
|
Sign up to set email alerts
|

Prospective validation of a novel renal activity index of lupus nephritis

Abstract: Objectives The Renal Activity Index for Lupus (RAIL) score was developed in children with lupus nephritis (LN) as a weighted sum of six urine biomarkers (RAIL-UBMs) [neutrophil gelatinase associated lipocalin, monocyte chemotactic protein 1, ceruloplasmin, adiponectin, hemopexin and kidney injury molecule 1] measured in a random urine sample. We aimed at prospectively validating the RAIL in adults with LN. Methods Urine from 79 adults was collected at the time of kidney biopsy to assay the RAIL-UBMs. Using R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…With the exception of osteopon- tin, these are all validated biomarkers of LN activity and its response to therapy [12, 13, 15, 16]. Accordingly, none of these biomarkers was closely associated with NIH-CI scores in this study.…”
Section: Discussionmentioning
confidence: 62%
“…With the exception of osteopon- tin, these are all validated biomarkers of LN activity and its response to therapy [12, 13, 15, 16]. Accordingly, none of these biomarkers was closely associated with NIH-CI scores in this study.…”
Section: Discussionmentioning
confidence: 62%
“…Urinary KIM-1 was reported to elevated in active LN patients and correlate with renal histological inflammation [ 35 ]. More recently, KIM-1 has been validated as an important component in several different urinary biomarker panels including RAIL for predicting renal pathology [ 36 38 ]. In the current study, we also demonstrated that when combined with other UBMs, KIM-1 was able to better reflect renal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary NGAL has been validated as a predictor of renal disease activity [ 19 , 39 ], which has been confirmed in the current study. It is also one of the 6 UBMs in RAIL [ 36 , 38 ] that predict renal pathology AI in LN patients. More recently, Satirapoja et al demonstrated that baseline uNGAL performed better than conventional markers in predicting a treatment response in active LN patients with both sensitivity and specificity around 70% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, urine biomarkers of lupus nephritis have been discovered and validated for use in children and adults. The Renal Activity Index for Lupus quantifies lupus nephritis activity based on levels of several protein biomarkers measured in the urine 56–58. For capturing joint inflammation with cSLE, the assessment of number of joints with active arthritis and joints with limited range of motion, as done for JIA,59 has face validity.…”
Section: Organ-specific Assessments Of Csle Response To Therapymentioning
confidence: 99%